Synthesis and characterisation of Sr1.2Nd0.8Mn0.6Rh0.4O4 - Gallon, D; Battle, P; Blundell, S; Coldea, A; Rosseinsky, M; Steer, C (2003)
A polycrystalline sample of Sr1.2Nd0.8Mn0.6Rh0.4O4 has been synthesised and characterised by neutron diffraction, dc magnetometry, muon spectroscopy and magnetotransport measurements. Ir is an n = 1 member of the Ruddlesden-Popper (RP) An + 1BnO3n + 1 family, having tetragonal (I4/mmm) symmetry [a = 3.86418(6), c = 12.4414(2) Å]. Rh and Mn cations are disordered over the six-coordinate sites within the perovskite layers of the RP structure and the A sites are occupied by a disordered distribution of Nd and Sr. In contrast to the analogous compound Sr1.2La 0.8Mn0.6Rh0.4O4, which showed long range ferromagnetic ordering in an applied field ar 2 K, a spin-glass transition was observed ar 16 K for the Nd-containing compound. No long range magnetic order was observed ar 2 K. A maximum magnetoresistance of ∼ 30% in a 140 kOe field was found at 125 K.